Human/Robot communication through the application of bio-electrical signal interfaces - Ierache, Jorge Salvador (2012)
This article shows the experiences carried out in the context of human/robot communication, on the basis of brain bio-electrical signals, with the application of the Brain-Machine Interface from NIA. There are available technologies and interfaces which have facilitated the reading of the user’s brain bio-electrical signals and their association to explicit commands that have allowed the control of biped and mobile robots (NXT-Lego) through the adaptation of communication devices. Our work presents an engineering solution, with the application of technological bases, the development of communication framework local and remote control, the description of experiments and the discussion of the results achieved in field tests. Finally, the Brain-Machine Interface (BMI) from Emotiv is presented.